The significance of serum midkine in the diagnosis and prognosis of invasive ductal carcinoma of the breast - Al-Huda Muhammad, Noor J; Jabbar, Haider A; Kazem, Nahidh R (Vojenské zdravotnické listy, 2024)
Background and Objectives: Initial diagnosis of brest cancer (BC) is important for fate and prognosis of the diseases profile, we sought to identify the correlation between Midkine (MK) as a new biomarker with cancer antigen (CA)15-3, liver function test, renal function test, blood cells parameters in individuals with invasive ductal carcinoma.Methods: The serum MK and CA15-3 of all subjects were measured by the ELISA technique, Liver enzymes were measured by colourimetric methods and neutrophils, and lymphocytes were measured by an Electrical Impedance Cell Counting method (automated machine).Results: The results of the correlation among serum MK and other parameters in invasive ductal carcinoma of the breast showed a considerable positive correlation among MK and CA15-3 and measured white blood cells. Moreover, there were a weak correlation with Aspartate Aminotransferase (AST) and RBC, while there is no correlation between serum MK and other liver enzymes or blood parameters. Conclusion: The study results of the correlation between serum MK and other parameters in colorectal carcinoma patients show a significant positive correlation of MK with CA15-3 markers in invasive ductal carcinoma of the breast.
Keywords: Humans; duktální karcinom prsu; Lymphocytes; lymfocyty; Biomarkers, Tumor; klinická studie jako téma; Clinical Studies as Topic; Liver Function Tests; jaterní testy; ELISA; neutrofily; lidé; midkin; Enzyme-Linked Immunosorbent Assay; Carcinoma, Ductal, Breast; nádorové biomarkery; Midkine; Breast Neoplasms; Neutrophils; nádory prsu; vyšetření funkce ledvin; Kidney Function Tests